Seductions of Place Geographical Perspectives on Globalization and Touristed Landscapes - Lew, Alan A. 1955- (Routledge, 2005)
The seductiveness of touristed landscapes is simultaneously local and global, as travelled places are formed and reworked by the activities of diverse, mobile people, in their desires to experience situated, sensuous qualities of difference. Cartier and Lew's interesting and informative book explores contemporary issues in travel and tourism and human geography, and the complex cultural, political, and economic activities at stake in touristed landscapes as a result of globalization. This book assesses travel and tourism as simultaneously cultural and economic processes, through ideas about place seduction and the formation of landscapes. Throughout, examples are given from urban and environmental touristed landscapes, from major world cities to tropical islands, and chapter contributions include: an analysis of the representational character of landscape and the built environment historic constructions of place seduction the importance of class, racial, and gender dimensions of place how mobility and the seduction of place orient identity formation the environmental impacts of tourism economies. Broad in scope, this book is ideal for social scientists and humanists who are interested in contemporary debates about place studies, mobility, and the located realities of globalization